Activation of blood coagulation after cardiac arrest is not balanced adequately by activation of endogenous fibrinolysis - Böttiger, Bernd W.; Motsch, Johann; Böhrer, Hubert; Böker-Blum, Thomas; Aulmann, Michael; Nawroth, Peter Paul; Martin, Eike (Circulation, 1995)
Background Animal studies have demonstrated that hemostatic disorders occurring after cardiac arrest affect outcome. We investigated hemostatic changes during and after cardiopulmonary resuscitation (CPR) in humans. - - Methods and Results The prospective study included 23 patients (29 to 86 years) who underwent out-of-hospital CPR for nontraumatic causes. Blood samples were drawn immediately and 15 and 30 minutes after initiation of CPR. In the case of restoration of spontaneous circulation (ROSC; n=7), additional blood samples were taken immediately, 30 minutes, and 2, 8, 24, 48, and 72 hours after ROSC. A marked activation of blood coagulation was found in all patients. The specific markers of activated blood coagulation and fibrin formation, thrombin-antithrombin complex (TAT; median during CPR, 260 μg/L; median after ROSC, 57 μg/L; normal range, 1.0 to 4.1 μg/L), and fibrin monomers (FM; median during CPR, 34.3 μg/mL; median after ROSC, 65.4 μg/mL; normal range, 0 to 3.6 μg/mL) were markedly increased during and in the early phase after CPR. When patients survived for 48 hours, TAT and FM values returned to the normal range. In most patients, the plasma levels of d-dimer, an indicator of endogenous fibrinolytic activity, were not markedly increased during CPR (median, <0.25 μg/mL; normal range, <0.25 μg/mL) but increased moderately after ROSC (median, 0.56 μg/mL). Levels of plasminogen activator inhibitor type 1 (normal range, 0.3 to 3.5 U/mL), a marker for endogenous inhibition of fibrinolytic activity, were moderately increased in most patients (median during CPR, 4.22 U/mL; median after ROSC, 8.08 U/mL). - - Conclusions Our data clearly demonstrate that there is a marked activation of blood coagulation and fibrin formation after prolonged cardiac arrest and CPR in humans that is not balanced adequately by concomitant activation of endogenous fibrinolysis. These changes may contribute to reperfusion disorders, such as the cerebral “no-reflow” phenomenon, by inducing fibrin deposition and formation of microthrombi.